Learning for the NHS on procurement and supply chain management: a rapid evidence assessment - Saba Hinrichs; Deepa Jahagirdar; Céline Miani; Benoit Guerin; Ellen Nolte (National Institute for Health Research, 2014)
Background: Procurement of clinical and non-clinical goods has been identified as one area for efficiency savings for the NHS. There is a need for robust evidence to help the NHS make informed decisions about how to make such savings and there is potential for lessons to be learned from activities and initiatives implemented elsewhere to enable the adoption of good practice. The work presented in this report seeks to contribute to this process by advancing our understanding of the evidence on procurement and supply chain management (SCM) in sectors within and outside health care that can inform practice in the NHS. Objectives: Principally drawing on a rapid evidence assessment (REA), we sought to (1) describe approaches to procurement and SCM in selected areas (including, but not limited to, manufacturing and automotive sectors, defence, information and communication technology, and pharmaceutical industries) and (2) identify best practices that may inform procurement and SCM in the NHS. Data sources: Searches were conducted across MEDLINE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Academic Search Complete, Social Sciences Abstracts, Military and Government Collection, EconLit and Business Source Complete from January 2006 to November 2013, and Google Scholar, Web of Science and Business Source Complete for articles on specific sectors. Methods: We conducted a REA of the published and grey literature in a range of non-health-care and health-care sectors from 2006 onwards. The review was complemented by interviews with a small set of purchasing stakeholders working within and with the NHS to help place the findings of the evidence review in the current NHS context, and a review of select experiences of procurement and SCM in New Zealand and France (chosen because of the likely application of their experiences in the NHS). Results: We identified a total of 72 studies for review. Findings highlighted that there is awareness in scholarly research and industry that SCM and procurement are areas for creating efficiencies and cost savings. We found that collective approaches to purchasing, improving relationships with suppliers, building capabilities and skills for purchasing decisions and the use of technology for data and materials management may lead to more efficient procurement and potentially save costs. Existing empirical evidence was scarce and, where available, tended to be weak in design and execution. Limitations: Given the nature and variety of subject areas covered, an iterative process was conducted to narrow the searches and apply a fairly restricted combination of search terms and cut-off date. Although this still yielded a large number of studies (13,191), it is possible that this approach missed studies that would have been of relevance for this review. Studies that reported empirical findings only were included for final review, but this definition was broadened to include single case studies in order to capture the limited cases of interventions in practice and find examples of what can be learned from practice rather than theory. Conclusions: Many of the studies identified are only described as before-and-after studies and do not include evaluations of their effects. We identified four recommendations for further research. First, there is a need for further research using rigorous methodology to assess the effectiveness of different types of interventions in different settings for improving purchasing and SCM. Second, empirical research on current practices in health-care purchasing and SCM, or evaluation of new practices in health-care settings, should be implemented. Third, an evaluation of the Department of Health's 2013 Procurement Development Programme and its recommendations provides an opportunity to focus future evaluation efforts. Finally, there is a need for increased interdisciplinary work across health-care management and SCM. Funding: The National Institute for Health Research Health Services and Delivery Research programme.